I'd hide you: performing live broadcasting in public - Reeves, Stuart; Greiffenhagen, Christian; Flintham, Martin; Benford, Steve; Adams, Matt; Farr, Ju Row; Tandavantij, Nick (ACM, 2015)
We present a study of a mixed reality game called 'I'd Hide You' that involves live video streaming from the city streets. We chart the significant challenges facing performers on the streets who must simultaneously engage in the game, stream compelling video footage featuring themselves, and interact with a remote online audience. We reveal how these street performers manage four key tensions: between their body and camera; between the demands of online audiences and what takes place on-the-street; between what appears 'frontstage' on camera versus what happens 'backstage'; and balancing being a player of the game with being a performer. By reflecting on how they achieve this, we are able to draw out wider lessons for future interfaces aimed at supporting people broadcasting video of themselves to online audiences while engaged in games, sports and other demanding real-world activities.